2012
DOI: 10.1007/s00414-012-0698-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of pulmonary surfactants and cytokines in drowning compared with other asphyxiation and fatal hypothermia

Abstract: Drowning involves complex fatal factors, including asphyxiation and electrolyte/osmotic disturbances, as well as hypothermia in cold water. The present study investigated the molecular pathology of pulmonary injury due to drowning, using lung specimens from forensic autopsy cases of drowning (n = 21), acute mechanical asphyxia due to neck compression and smothering (n = 24), and hypothermia (cold exposure, n = 11), as well as those of injury (n = 23), intoxication (n = 13), fire fatality (n = 18), and acute ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…Such autopsy data is important for understanding the pathophysiology of human death; however, it has been reported that the stability of housekeeping gene expressions may be different among the tissues and affected by the cause of death, suggesting that at least four endogenous references should be used in human postmortem cardiac muscle, skeletal muscle and brain [38]. Although our preliminary experiments using human postmortem lung tissue showed good correlations among commonly used housekeeping genes, including B2M, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and betaactin (unpublished data), as well as gradual and parallel degradation with target genes [39], further cooperation and investigation will be needed to establish the efficacy of individual endogenous references in practical application.…”
Section: Discussionmentioning
confidence: 89%
“…Such autopsy data is important for understanding the pathophysiology of human death; however, it has been reported that the stability of housekeeping gene expressions may be different among the tissues and affected by the cause of death, suggesting that at least four endogenous references should be used in human postmortem cardiac muscle, skeletal muscle and brain [38]. Although our preliminary experiments using human postmortem lung tissue showed good correlations among commonly used housekeeping genes, including B2M, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and betaactin (unpublished data), as well as gradual and parallel degradation with target genes [39], further cooperation and investigation will be needed to establish the efficacy of individual endogenous references in practical application.…”
Section: Discussionmentioning
confidence: 89%
“…Accurate and reliable relative RT-qPCR requires ideal amplification efficiencies of target and reference genes [10]; selection of adequate reference genes is essential. Previous studies suggested successful application of conventional reference genes for the myocardium, lungs, kidneys, and skeletal muscle [7,[11][12][13][14]. For estimating the amplification efficiency, however, conventional standard curve method is time consuming, requiring the production of repeatable and reliable standards [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the presence of aggregates of surfactant protein A would suggest mechanical asphyxia or drowning, and their absence would suggest an alternative cause of death. Messenger RNA has also been studied in these cases, but there is limited information with this method [20]. …”
Section: Resultsmentioning
confidence: 99%